Zaman Menuntut Konselor Menjadi Kreatif - Eko Susanto; Ade Hidayat (Indonesian Journal of Educational Counseling, 2018)
DEMANDS: COUNSELORS TO BE CREATIVE. Along with the development era of counselor, work demands become increasingly complex. Challenges will be constantly confronted by counselors as a result of the changes taking place. Changes in the work environment of counselors force them to be creative. Counselors should be able to find solutions, find new ways and adapt to changes that occur. So, on the process of education of potential counselors in Indonesia should also encourage the creativity of counselors in the realm of their scope of work. Such efforts need to be integrated with the counselor education curriculum. One of them is developing the SCAMPER Model to help candidate of counselors and professional counselors in Indonesia encourage their creativity.